Modelling damage growth in composites subjected to impact and compression after impact. (15th May 2017) - Abir, M.R.; Tay, T.E.; Ridha, M.; Lee, H.P.
Abstract: Compression After Impact (CAI) tests are frequently performed to characterize the effect of impact damage on strength of composites. This paper presents an integrated single finite element model that enables analysis of impact damage and CAI without major simplifications and idealizations of damage in composites. When applied to a series of quasi-isotropic laminates, the results obtained from simulation correlate well with experiment with regards to damage shapes, sizes and CAI strength. Failure during CAI was found to be triggered by local buckling, causing fibre and delamination damage growth (during compression) that leads to rapid and sudden load drop. Compressive strength, Mode I fibre compressive fracture toughness and Mode II interlaminar fracture toughness were found to be the key parameters that affect residual strength of composites. Such models can lead to a better understanding of damage growth mechanisms necessary for development of damage tolerant structures, as well as promote virtual testing, with considerable cost and time savings.